The Immigrant Wage Gap in Germany: Are East Europeans Worse Off? - Florian Lehmer; Johannes Ludsteck (European Regional Science Association (ERSA), 2010)
This study compares the outcomes of male foreign workers from different East and West European countries who entered the German labour market between 1995 and 2000, with those of male German workers. We find that the immigrant-native wage gap differs significantly between nationalities: the differential is largest for workers from Poland (-44 percent) and the Czech Republic (-38 percent) and by far the lowest for Spaniards (-8 percent). Results from an Oaxaca/Blinder type decomposition show that unfavourable characteristics (compared with German workers) contribute significantly to the explanation of the immigrant wage gap. This is especially true for workers from Poland, Portugal, Italy and Slovakia. For all other countries, it is observed that the coefficients effect dominates. It can therefore be concluded, that immigrants are generally affected by "discrimination". Comparing the effects for workers from East European EU member countries with those for other nationality groups, it emerges that East Europeans are not worse off than other nationalities. The most pronounced "discrimination" is found for immigrants from non-EU states in Eastern Europe. To analyse the importance of segregation into sectors, we take a closer look at construction and hotels & restaurants and find that the coefficients effect still adds most to the explanation of the raw wage differential between foreigners and Germans. This indicates that segregation into sectors does not significantly contribute to the "discrimination" of foreigners. Additional information is obtained from quantile decompositions. Coefficient effects (in absolute values) decrease for the majority of countries. Thus, discrimination appears to be more pronounced at low wage levels. Moreover, this evidence suggests sticky floors rather than glass ceilings.
Keywords: J61; J31; J15; 330; East Europeans; immigration; wage gap; (quantile) decomposition; EU enlargement; sticky floors